Material didáctico tecnológico para el octavo año de educación básica de la asignatura de estudios sociales del bloque “la vida económica” en la unidad educativa Bernardo Valdivieso del cantón Loja, provincia de Loja, periodo lectivo 2015-2016 - Troya Muñoz, Ramiro Fabián (2016)
This paper titled MATERIAL DIDÁCTICO TECNOLÓGICO PARA EL OCTAVO AÑO DE EDUCACIÓN BÁSICA DE LA ASIGNATURA DE ESTUDIOS SOCIALES, DEL BLOQUE “LA VIDA ECONÓMICA” EN LA UNIDAD EDUCATIVA BERNARDO VALDIVIESO DEL CANTÓN LOJA, PROVINCIA DE LOJA, PERIODO LECTIVO 2015-2016, originated from the need to apply knowledge acquired in the academic formation of the Educational Information career and to meet the requirement for the degree. A notorious problem that is of concern to both teachers, parents and students is the lack of teaching aids and technology to the process of learning of the subject of Social Studies, one reason being the lack of planning and teaching methodology and who go several years and still continue with the same traditional pedagogy of learning, years ago, without introducing such means and resources, in addition to the carelessness and lack of entrepreneurship by teachers to investigate and updated in new techniques and methods education, this in itself leads to insufficient fluidity by educators to youth. Given this general objective which allowed investigate the impact of the application of technological training materials for the eighth year of basic education in the subject of Social Studies, the block "La Vida Económica" in the Educational Unit "Bernardo Valdivieso" from the raised Canton Loja, Loja province, academic year 2015-2016. Scientist: To perform a structured way this research were used five methods that served to generate the problem under study for literature and the theoretical framework will be formulated; Inductive: they use it to silver conclusions by observing and recording all the facts; Deductive who helped to observation, creating a hypothesis and explain the problem; Statistical: that it was to apply, collect, organize and analyze numerical data; and Analytical: that served to analyze the information. Finally conclusions and recommendations were developed, which are summarized as follows: 100% teachers use traditional teaching materials, together with technological equipment; while 25% use technological nature itself for the subject of Social Studies; and the Proposal for Technology Training Material for Block economic life, improve the teaching-learning process. Whereupon it is recommended that: technological teaching materials are introduced into the classroom from the teacher to measure distance himself in traditional education and to run the letter calls this proposal for teaching materials.